2010
DOI: 10.1258/ijsa.2010.010061
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and genital warts: an unhappy coalition

Abstract: Through clinical practice, it is often perceived that patients with diabetes are more likely to suffer from severe and recalcitrant warts. This study was set up to investigate if genital warts were more common in patients with diabetes and to determine if patients with diabetes and genital warts required more treatment than those without diabetes. Only female patients with diabetes and genital warts were investigated and were compared to the non-diabetic population. Results suggested that patients with diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…These are duration of wart, site of wart, size of wart, type of wart, previous treatment, age of the patient, concomitant illness and smoking. 7 In this study, we found that patients with more than 30 years of age and chronic smokers have reduced the clearance rate of wart in group B and C. Similar to our study Horn et al has found significant correlation between age and clearance of wart. 8 On the contrary Gamil et al and Fahime Khozeimeh et al stated that age had no effect on the therapeutic response in immunotherapy treated warts.…”
Section: Discussionsupporting
confidence: 90%
“…These are duration of wart, site of wart, size of wart, type of wart, previous treatment, age of the patient, concomitant illness and smoking. 7 In this study, we found that patients with more than 30 years of age and chronic smokers have reduced the clearance rate of wart in group B and C. Similar to our study Horn et al has found significant correlation between age and clearance of wart. 8 On the contrary Gamil et al and Fahime Khozeimeh et al stated that age had no effect on the therapeutic response in immunotherapy treated warts.…”
Section: Discussionsupporting
confidence: 90%
“…Guidance for daily practice situations and the subsequent action that can be taken are shown in Table …”
Section: Methodsmentioning
confidence: 99%
“…• Determine if the patient has other conditions, such as diabetes, which are associated with more extensive AGW and recurrences that may require prolonged treatment 80 • More ablation and prolonged imiquimod courses may be required • It is recommended not to use imiquimod if there is eczema, psoriasis or other dermatoses in the genital area 77 to pre-treat the AGW with an immunotherapy for 2 months to see whether an immune response can be stimulated. If the warts are still present following this treatment, an ablative technique can be used to remove the AGW.…”
Section: Heavy Cigarette Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, patients with T2D are at increased risk of HPV-associated cancers, including cervical cancer and head and neck cancer 1820 . Moreover, diabetic patients develop more extensive HPV-related genital warts and they are more prone to disease recurrence as compared to non-diabetic subjects 21 . In addition to epidemiological observations, our group has successfully shown that diabetes could act as a co-factor to promote HPV-driven tumorigenesis in db/db mice bearing CUP-1 (HPV-16 E7 transformed) xenograft 22 .…”
Section: Discussionmentioning
confidence: 99%